Electrical transport measurements for superconducting sulfur hydrides using boron-doped diamond electrodes on beveled diamond anvil. (29th October 2020) - Matsumoto, Ryo; Einaga, Mari; Adachi, Shintaro; Yamamoto, Sayaka; Irifune, Tetsuo; Terashima, Kensei; Takeya, Hiroyuki; Nakamoto, Yuki; Shimizu, Katsuya; Takano, Yoshihiko
Abstract: A diamond anvil cell (DAC) has become an effective tool for investigating physical phenomena that occur at extremely high pressure, such as high-transition temperature superconductivity. Electrical transport measurements, which are used to characterize one of the most important properties of superconducting materials, are difficult to perform using conventional DACs. The available sample space in conventional DACs is very small and there is an added risk of electrode deformation under extreme operating conditions. To overcome these limitations, we herein report the fabrication of a boron-doped diamond microelectrode and undoped diamond insulation on a beveled culet surface of a diamond anvil. Using the newly developed DAC, we have performed in-situ electrical transport measurements on sulfur hydride H2 S, which is a well-known precursor of the pressure-induced, high-transition temperature superconducting sulfur hydride, H3 S. These measurements conducted under high pressures up to 192 GPa, indicated the presence of a multi-step superconducting transition, which we have attributed to elemental sulfur and possibly HS2 .